Susut Bobot dan Kadar Air Tajuk Tanaman Pakcoy Akibat Pengaruh Jenis Media Tanam dan Konsentrasi Nutrisi AB Mix : Weight Loss and Moisture Content of Pakcoy Plant Shoots Due to the Influence of Growing Media Types and AB Mix Nutrient Concentration - Triani, Nova; Lestari, Rizky Wahyu (Agrocentrum, 2024)
Pakcoy (Brassica rapa subsp. chinensis) is a type of vegetable commonly cultivated using hydroponic systems. The weight loss and moisture content of pakcoy plant shoots can be influenced by the type of growing media and the concentration of AB Mix nutrients. Each type of growing medium has distinct physical and chemical properties. The combination of different AB Mix nutrient concentrations with various growing media types results in varying weight loss and moisture content in the plant shoots. Pakcoy plants with lower weight loss and higher shoot moisture content exhibit better storage resistance. The research method employed was a Factorial Randomized Block Design with two factors: the first factor being the type of growing media (burnt rice husk, cocopeat, rockwool), and the second factor being the concentration of AB Mix nutrients (1,000, 1,200, and 1,400 ppm). The results indicated that rockwool, combined with an AB Mix nutrient concentration of 1,000 ppm, resulted in the lowest weight loss and the highest shoot moisture content compared to other treatments.